The Effectiveness of Integrating Gamification and Project-Based Learning to Enhance Student Engagement and Value Internalization in High School Islamic Education - Muhammad Aldam Shaka Pradipta; Marwal Blantara Susetyo; Nurti Budiyanti; Syifa Fatihatul Mubarokah; Helmy Abdullah Helmy (Jurnal al-Thullab, 2026)
Islamic Religious Education (PAI) in Indonesian senior high schools faces persistent challenges of low student engagement and superficial value internalization, largely resulting from conventional teaching methods that rely on dogmatic delivery and rote memorization. This study aims to evaluate the pedagogical effectiveness of integrating gamification and project-based learning in enhancing student engagement and facilitating authentic value internalization within high school PAI. A qualitative single case study design was employed at a senior high school in Bandung, involving 34 students selected through purposive intensity sampling. Data were gathered through the triangulation of in-depth interviews, focus group discussions, and participant observation, then analyzed using interactive thematic analysis. The findings reveal that gamification significantly reduced academic anxiety and increased emotional engagement, creating a psychologically safe classroom climate. This affective readiness was subsequently leveraged by project-based learning, where direct engagement in authentic social projects triggered deep social empathy and spontaneous behavioral commitments that extended beyond academic requirements. The synergy of these methods produced a qualitatively distinct learning experience that facilitated organic value internalization without external pressure. This study contributes to Islamic education scholarship by offering a student-centered pedagogical model that integrates emotional engagement with concrete character actualization, challenging the dominance of conventional rote learning and providing actionable implications for PAI curriculum redesign and teacher professional development.